Comparison of the Effects of Anesthesia with Isoflurane and Total Intravenous Anesthesia on the Intensity of Body Temperature Reduction during Anesthesia and Incidence of Postoperative Chills - Zahid Hussain Khan; Saghar Arab; Behruz Emami (Acta Medica Iranica, 2011)
"nThis study compared the effects of anesthesia with isoflurane and TIVA (total intravenous anesthesia) on the intensity of body temperature reduction during anesthesia and incidence of chills after lumbar disc surgery. The study was done as a single blinded randomized clinical trial. From 60 patients who underwent lumbar disc surgery, 30 subjects were placed in isoflurane group and 30 in the TIVA group. Maintenance of anesthesia was done with isoflurane (MAC=0.8-1) and N2O 50% in isoflurane group and in TIVA group with propofol at the dose of 100-150 mg /kg body weight /minute and remifentanil at the dose of 2.0 mg /kg body weight/minute. Chills rate was recorded in recovery room. Changes in body temperature, body surface temperature, systolic blood pressure, diastolic blood pressure and heart rate showed no significant difference between the two groups before and after induction and at different times during the operation (P<0.05). Chill rate was not significantly different between the two groups (P<0.05). It seems that TIVA (remifentanil at the dose of 2.0 µg/kg body weight/minute in combination with propofol at the dose of 100-150 µg/kg body weight/minute) and 0.81 MAC isoflurane-N2O 50% can be used as a safe method of anesthesia in patients with good tolerance lumbar back disc surgery without hypothermia, chills and considerable hemodynamic changes.